Vitamin K-3 family members - Part II: Single crystal X-ray structures, temperature-induced packing polymorphism, magneto-structural correlations and probable anti-oncogenic candidature - Rane, Sandhya; Ahmed, Khursheed; Salunke-Gawali, Sunita; Zaware, Santosh B.; Srinivas, D.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Journal of Molecular Structure, 2008)
Temperature-induced packing polymorphism is observed for vitamin K-3 (menadione, 3-methyl-1,4-naphthoquinone, 1). Form la crystallizes at 300 K and 1b at 277 K both in the same space group P2(1)/c. Form 1b contains one molecule per asymmetric unit, performing anisotropy in g-factor viz. g(z) = 2.0082, g(y) = 2.0055 and g(x) = 2.0025, whereas form 1a contains two molecules in its asymmetric unit. Vitamin K-3 family members 2, [2-hydroxy vitamin K-3] and 3, [2-hydroxy-1-oximino vitamin K-3] also perform intrinsic neutral active naphthosemiquinone valence tautomers even in dark having spin concentrations due to hydrogen bonding and aromatic stacking interactions which are compared to vitamin K-3. The significant lateral C-H center dot center dot center dot O and O-H center dot center dot center dot pi bifurcated or pi-pi(center dot) interactions are discussed for molecular associations and radical formations. X-ray structure of 3 revealed pi-pi(center dot) stack dimers as radicals signatured in PR as triplet with five hyperfine splits [(A) over bar(N-14) = 11.9 G]. The centrosymmetric biradicals in 3 show diamagnetism at high temperature but below 10 K it shows paramagnetism with mu(eff) as 0.19 B.M. Vitamin K-3 and its family members inhibit biological activities of acid phosphatase (APase), which are proportional to their spin concentrations. This may relate to their probable anti-oncogenic candidature in future. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Anti-oncogenic candidature; H-bonding; Magneto-structural correlations; Naphthosemiquinones in vitamin K-3 family; Packing polymorphism; Spin concentrations